Inverse associations of the lifestyle critical 9 with cardiorenal syndrome: the mediating role of the dietary inflammatory index - Li, Hongman; Li, Long (Frontiers in Nutrition, 2025)
BackgroundCardiorenal syndrome (CRS) represents a burgeoning global health concern characterized by its increasing prevalence. Life’s Crucial 9 (LC9), an innovative tool for cardiovascular health assessment, and the Dietary Inflammatory Index (DII), which quantifies diet’s impact on body inflammation, have not been previously studied in conjunction regarding their association with CRS.ObjectiveThis study aims to explore the relationship between LC9 and CRS, using data from the National Health and Nutrition Examination Survey (NHANES), and to examine whether DII serves as a mediator in this association.MethodsThis research included data from 25,792 NHANES participants spanning from 2005 to 2018. The study leverages the dataset’s comprehensive representativeness and robust statistical power to ensure generalizable and reliable findings. We employed weighted logistic regression to evaluate the association between LC9 scores and CRS presence, conducted subgroup analyses, and performed mediation analysis to investigate the role of DII.ResultsOur analysis demonstrated a significant inverse relationship between LC9 and CRS. Upon controlling for confounders, each 10-point rise in LC9 correlates with a 26% reduction in CRS prevalence (p < 0.001). Additionally, stratifying LC9 into tertiles with T1 as the reference group revealed that T2 (OR = 0.59, 95% CI = 0.48–0.72, p < 0.001) and T3 (OR = 0.57, 95% CI = 0.38–0.88, p < 0.001) exhibited a strong negative correlation trend. The dose–response curve illustrates a linear relationship between LC9 and CRS; as LC9 increases, the occurrence of CRS decreases. DII shows a significant positive connection with CRS (p < 0.001), but DII indicates a decreasing trend when LC9 rises (β = −0.65, p < 0.001). Mediation analysis reveals that DII mediates the association between LC9 and CRS, with a mediation proportion of 12.5% (p < 0.001).ConclusionThe findings indicate a robust inverse correlation between LC9 scores and CRS incidence, with DII is associated with this relationship. This suggests potential preventive strategies against CRS through lifestyle modifications guided by LC9.